Negotiating Customary Law and Fiqh Norms: The Transformation of the Mepahukh Tradition in the Indigenous Marriage Practices of the Alas People in Southeast Aceh - Muhammad Adib Alfarisi; Raihan Putri; Dina Fadhila; Ezzerouali, Souad (Indonesian Journal of Sharia and Socio-Legal Studies, 2025)
Custom-based matchmaking practices in Muslim communities often experience tension between cultural authority and religious normative frameworks. However, comprehensive studies exploring the negotiation between local traditions and fiqh (Islamic jurisprudence) norms in contemporary contexts remain limited. This article examines the transformation of mepahukh, a customary courtship ritual performed during wedding celebrations among the Alas people in Southeast Aceh, through the lens of negotiation between customary law and fiqh-oriented norms. Utilizing a socio-legal approach and a fieldwork-based research design, this study draws on primary data collected through semi-structured interviews with eight key informants, including a village head, customary leaders, local religious authorities, and young people, as well as non-participant observation of the ritual’s implementation. The findings reveal that while mepahukh continues to function as a social mechanism for strengthening marital alliances and reproducing ethnic identity, it is increasingly subject to normative scrutiny due to negative perceptions of ikhtilāṭ (unsupervised interaction between non-maḥram men and women) and concerns regarding moral permissiveness. In response to growing criticism from religious authorities, the Alas community has adopted adaptive strategies, including family deliberations, procedural restrictions, and enhanced roles for customary and religious leaders. This article argues that mepahukh is not a static cultural artifact but a dynamic space for value negotiation within the inter-legalities between customary and Islamic law. The sustainability of this tradition depends on the community’s ability to reformulate its practices in ways that are ethical, context-sensitive, and aligned with both cultural norms and religious principles. [Praktik perjodohan berbasis adat dalam masyarakat muslim kerap menghadapi ketegangan antara otoritas kultural dan kerangka normatif agama. Namun demikian, kajian komprehensif yang secara mendalam mengeksplorasi dinamika negosiasi antara tradisi lokal dan norma fikih dalam konteks kontemporer masih relatif terbatas. Artikel ini menganalisis transformasi tradisi mepahukh—sebuah ritus perjodohan adat yang dilaksanakan pada malam hari dalam rangkaian pesta perkawinan masyarakat Alas di Aceh Tenggara—dalam kerangka negosiasi antara hukum adat dan norma-norma fikih. Dengan menggunakan pendekatan sosio-legal dan desain penelitian berbasis lapangan, artikel ini mengandalkan data primer dari wawancara semi-terstruktur dengan delapan informan kunci, yang terdiri atas kepala desa, tokoh adat, otoritas keagamaan, dan pemuda-pemudi yang terlibat, serta observasi non-partisipatif terhadap pelaksanaan tradisi tersebut. Temuan menunjukkan bahwa meskipun mepahukh tetap berfungsi sebagai mekanisme sosial untuk membentuk aliansi pernikahan dan mereproduksi identitas etnik, praktik ini semakin mendapat tekanan normatif akibat persepsi negatif terhadap ikhtilāṭ (interaksi bebas antara laki-laki dan perempuan non-mahram) dan kekhawatiran atas kemerosotan moral. Merespons kritik dari kalangan tokoh agama, komunitas Alas menunjukkan kapasitas adaptif melalui musyawarah keluarga, pembatasan teknis, serta penguatan peran tokoh adat dan agama. Artikel ini berargumentasi bahwa mepahukh bukanlah artefak budaya yang statis, melainkan ruang negosiasi nilai yang berlangsung dalam konteks interlegalitas antara hukum adat dan norma fikih. Keberlanjutan tradisi ini bergantung pada kapasitas komunitas untuk mereformulasi praktiknya secara etis, kontekstual, dan selaras dengan prinsip budaya maupun agama.]